2017
DOI: 10.1007/s11356-017-8781-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mineral contents, particle matter and bottom ash distribution during pellet combustion: molar balance and chemometric analysis

Abstract: This paper aims to identify the correlation between the mineral contents in agropellets and particle matter and bottom ash characteristics during combustion in domestic boilers. Four agrifood residues with higher mineral contents, namely grape marc (GM), tomato waste (TW), exhausted olive mill solid waste (EOMSW) and olive mill wastewater (OMWW), were selected. Then, seven different pellets were produced from pure residues or their mixture and blending with sawdust. The physico-chemical properties of the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Such behavior may be attributed to the catalytic effect of minerals provided by OMWW after the impregnation process. The role of mineral contents on the gasification of biomass char is well identified in the literature [13], especially for the K element which is has a high catalytic effect [17,18,36] and it is the major mineral component as it is shown in Table 1. Similar investigations were performed by Guizani et al [37] for beech wood chips in the same experimental device.…”
Section: Effect Of the Pellets Properties On The Pyro-gasification Rementioning
confidence: 89%
“…Such behavior may be attributed to the catalytic effect of minerals provided by OMWW after the impregnation process. The role of mineral contents on the gasification of biomass char is well identified in the literature [13], especially for the K element which is has a high catalytic effect [17,18,36] and it is the major mineral component as it is shown in Table 1. Similar investigations were performed by Guizani et al [37] for beech wood chips in the same experimental device.…”
Section: Effect Of the Pellets Properties On The Pyro-gasification Rementioning
confidence: 89%
“…Table 2 shows that inorganic elements (Na, K and Ca) are highly concentrated in the EOMSW, EOMSW-OMWW and PS-OMWW samples. This elevated concentration is not only due to the initial amount of Na, K and Ca in raw material EOMSW but also due to impregnation process when using OMWW (rich of these minerals) [30,31]. It is worth noting that these higher inorganic contents are very interesting of point of view catalytic effect during gasification process [31e33].…”
Section: Samples Characterizationmentioning
confidence: 99%
“…This correlation is linear with a regression factor R 2 = 0.94. Also, in the same context Jeguirim et al [38] have shown a linear correlation between the total PM (g/kg) and K and the sum (K + Na + S +Cl) expressed in g/kg. Furthermore, they found that the correlation with potassium is more strong with a correlation coefficient R 2 = 0.94 than with the sum (K + Na + S +Cl) for which R 2 is equal to 0.88.…”
Section: Combustion Parameters and Pollutant Emissionsmentioning
confidence: 72%